Inclusion of different levels of Ricinus communis L leaf blade meal in whole diets for sheep - Zamora, J.; del Viento, A.; Barrientos, L.; Palma, J. M. (Cuban Journal of Agricultural Science, 2020)
To evaluate different inclusion levels (0, 15, 30 and 45 %) of Ricinus communis leaf blade (LHRc) in whole sheep diets, four animals, with an initial weight of 27.37 ± 1.70 kg were housed in individual cages. Periods of 20 days were used. The first 15 days were used for diet adaptation, and the last five for measurement. A 4 x 4 Latin square design was applied, with Tukey test (P <0.05) for the multiple analysis of means, plus the linear regression analysis. Variables total food intake (TFI/kg DM), leaf intake (g DM Ricinus communis/kg LW), daily weight gain (DWG/kg), food efficiency (FE/kg) and registration of poisoning signs, were studied. There was a statistical difference (P <0.05) in all variables. The best results were for 0% of Ricinus communis leaf blade (total feed intake 1,332 kg DM/day, daily weight gain 0.315 kg/day and food efficiency 0.254 kg), with respect to 45 % of LHRc (total food intake 0.881 kg DM/day, 12.2 g DM of Ricinus communis/ kg LW, daily weight gain 0.090 kg/day and food efficiency 0.096 kg). There was presence of diarrhea in this treatment, without compromising the life of animals. The rest of treatments shared statistical similarity. The inclusion of Ricinus communis leaf blade meal had a negative influence on dry matter intake of sheep, with a remarkable reduction in the 45% level, where there was also the presence of diarrhea, without causing deaths. Key words: forage, arboreal, tropic, sheep